The specter of genocide : mass murder in historical perspective - Gellately, Robert, 1943-; Kiernan, Ben (Cambridge University Press, 2003)
Leading international experts offer an up-to-date, comprehensive history and analyses of multiple cases of genocide and genocidal acts, with a focus on the twentieth century and extensive coverage of the post-1945 period - including the atrocities in the former Yugoslavia, Bali, Cambodia, Ethiopia, Rwanda, East Timor, and Guatemala.